Senataxin Attenuates DNA Damage Response Activation and Suppresses Senescence - Mingyang Li; Genbao Shao (MDPI AG, 2024)
Oxidative stress, driven by reactive oxygen species (ROS) such as hydrogen peroxide (H2O2), induces DNA double-strand breaks (DSBs) that compromise genomic integrity. The DNA Damage Response (DDR), primarily mediated by ATM and ATR kinases, is crucial for recognizing and repairing DSBs. Senataxin (SETX), a DNA/RNA helicase, is critical in resolving R-loops, with mutations in SETX associated with neurodegenerative diseases. This study uncovers a novel function of senataxin in modulating DDR and its impact on cellular senescence. Senataxin is shown to be crucial not only for DSB repair but also for determining cell fate under oxidative stress. SETX knockout cells show impaired DSB repair and prolonged ATM/ATR signaling detected by Western blotting, leading to increased senescence, as indicated by elevated β-galactosidase activity following H2O2 exposure and I-PpoI-induced DSBs. Wild-type cells exhibit higher apoptosis levels compared to SETX knockout cells under H2O2 treatment, suggesting that senataxin promotes apoptosis over senescence in oxidative stress. This indicates that senataxin plays a protective role against the accumulation of senescent cells, potentially mitigating age-related cellular decline and neurodegenerative disease progression. These findings highlight senataxin as a critical mediator in DDR pathways and a potential therapeutic target for conditions where cellular senescence contributes to disease pathology.